Shoulder tendon characteristics in disabled swimmers in high functional classes – Preliminary report. (January 2019) - Klich, Sebastian; Kisilewicz, Aleksandra; Pożarowszczyk, Beata; Zatoń, Marek; Kawczyński, Adam; Michener, Lori A.
Abstract: Objective: To characterize disabled swimmers in comparison to an able-bodied swimmers for (1) supraspinatus tendon thickness, (2) subacromial space and (3) occupation ratio. Design: Cross-Sectional Study. Setting: Research laboratory. Participants: Disabled swimmers with upper (DSw-Upper) (n = 8) and lower (DSw-Lower) (n = 7) extremity disorders. The DSw-Upper were classified in sports class S7-S8, while DSw-Lower in S9-S10. The control group had 15 able-bodied swimmers. Main outcome measures: Ultrasound images of (1) supraspinatus tendon in short axis and long axis, (2) subacromial space, and (3) occupation ratio. Results: A thicker supraspinatus tendon in short axis was observed in DSw-Upper versus C-Sw (p = 0.012) and DSw-Upper versus DSw-Lower (p = 0.018); and in long axis for DSw-Upper versus CSw (p = 0.0001), and DSw-Upper versus DSw-Lower (p = 0.002). There was a greater occupation ratio in DSw-Upper versus DSw-Lower in short axis (p = 0.013) and long axis (p = 0.035). Conclusions: The present study showed a thicker supraspinatus tendon and greater occupation ratio with the tendon occupying more of the subacromial space that may predispose upper extremity disabled swimmers to tendon disorders such as subacromial impingement syndrome. Ultrasound examination can be used to assess shoulder tendon characteristics and the relationship to the subacromial space, to determine potential for injury and training load monitoring. Highlights: Ultrasound examination can be used to assess and monitor shoulder tendon characteristics in disabled swimmers. Thicker supraspinatus tendon and a greater occupation ratio with the tendon occupying more of the subacromial space. Disabled swimmers with upper extremity disorders have shoulder deficits related to subacromial impingement syndrome.